2021
DOI: 10.1007/s13204-020-01624-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of Ag plasmonic structures on garnet substrates

Abstract: In this paper technological aspects of preparation of silver nanostructures on garnet substrates and their impact on absorption and photoluminescence have been studied. For this purpose, the changes of plasmonic properties as a function of the Ag NPs preparation features, such as type of substrate material, sputtered silver mass thickness, temperature, and time of thermal treatments were shown. The plasmonic structures were prepared on single-crystalline YAG and GGG garnets as well as amorphous glass substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…In order to understand the luminescent properties of the Ag islands on the Si(111) surface, STML measurements are performed on Ag thin film of a thickness of 3 nm on the Si surface and Ag(111) single crystal. The STML spectra on these surfaces in figure 3 appear quite different to each other due to the plasmon resonance wavelength being strongly dependent on the surrounding material [22], while the curve fittings of the spectra demonstrate several distinguishing features. As expected, the absence of the P 1.85 on the spectrum of the Ag single crystal further confirms that this light emission indeed originates from the Si(111) surface.…”
Section: Resultsmentioning
confidence: 92%
“…In order to understand the luminescent properties of the Ag islands on the Si(111) surface, STML measurements are performed on Ag thin film of a thickness of 3 nm on the Si surface and Ag(111) single crystal. The STML spectra on these surfaces in figure 3 appear quite different to each other due to the plasmon resonance wavelength being strongly dependent on the surrounding material [22], while the curve fittings of the spectra demonstrate several distinguishing features. As expected, the absence of the P 1.85 on the spectrum of the Ag single crystal further confirms that this light emission indeed originates from the Si(111) surface.…”
Section: Resultsmentioning
confidence: 92%
“…Firstly, reducing the size distribution of NPs may be valuable in narrowing the mode linewidth. Studying the impact of Ag/dielectric layer thicknesses and annealing parameters on the morphology of the formed NPs would be an efficient way to achieve this [22]. Secondly, the resonance linewidth of dielectric NPs is not limited by absorption losses compared to metals, so replacing Ag NPs with dielectric NPs for enhanced scattering may be a promising direction [36].…”
Section: Discussionmentioning
confidence: 99%
“…The moderate thermal annealing treatment can transform the Ag films into discrete NPs (Ag NPs metasurface structure). A previous study has demonstrated that both the annealing condition and coating thicknesses of Ag films can affect the morphology and distribution of the formed Ag NPs, which consequently affect the overall resonance performance of the Ag NPs metasurface structures [22]. To simplify, we fix the annealing conditions, so the distribution of the formed Ag NPs is mainly determined by the thickness of the deposited Ag film.…”
Section: Experiments Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…New methods for investigating the interaction between metallic nanoparticles and excited uorophore were discovered through the rapid development of nanotechnology science over the last decades. The interactions between the metallic nanoparticles with uorophores had a growing interest in recent years [1,2]. The near eld interactions between uorophores and metallic nanoparticles help in modi cation of the uorescence emission [3,4].…”
Section: -Introductionmentioning
confidence: 99%